The effect of study skills on the academic performance of diploma in accountancy students of UiTM Sarawak / Josephine Avelind Noyem ... [et al.] - Noyem, Josephine Avelind; Juan, Delilah Samson; Kassim, Azalilah; Abdillah, Azlin; Rahmat, Mariam (Universiti Teknologi MARA, Sabah, 2022)
This study aims to examine the relationship between study skills and their effect on academic performance of Diploma in Accountancy students of Universiti Teknologi MARA Sarawak. This study covers a total of 142 selected final year students. Data were collected and analyzed using Kruskal-Wallis Test. Among the study skills, it was observed that the “Test Strategies and Test Anxiety” skill was significantly different between low performing and high performing students. Only Test Strategies and Test Anxiety skills affected students’ academic performance. An emphasis should be put on test-taking strategies and anxiety management in their early years of tertiary education as this could potentially influence their academic performance.